Actualization of Islamic Rules in Sharia Banking: A Review of Contemporary Issues in Jayapura, Indonesia - Ingratubun, H. M. Husni T. A (Hasanuddin Law Review, 2016)
This article aims to determine the applicable of Islamic rules in Sharia Banking of Jayapura. The study was conducted in Jayapura City, Papua, Indonesia with purposive sampling techniques which involving over 90 respondents from two Islamic banks, Bank Muamalah Indonesia (BMI) and Bank Syariah Mandiri (BSM). The research also involved some knowledgeable informants to give rich related information. The data were analysed by using the frequency table with the descriptive analysis. Results of the research revealed that the actualization is still facing a wide range of issues. Firstly, most of the customers have not clear or deep understanding of profit-and-loss sharing system. Secondly, they also do not know what advantages they would get if they do transactions in the BMI and BMS Jayapura. Besides that, it also indicated that most of the BMI and BSM customers decided to be member of the banks because of their fanatics to their religion and they are afraid of breaking the Islamic rules.